2022
DOI: 10.1038/s41467-022-28748-0
|View full text |Cite
|
Sign up to set email alerts
|

Tree functional traits, forest biomass, and tree species diversity interact with site properties to drive forest soil carbon

Abstract: Forests constitute important ecosystems in the global carbon cycle. However, how trees and environmental conditions interact to determine the amount of organic carbon stored in forest soils is a hotly debated subject. In particular, how tree species influence soil organic carbon (SOC) remains unclear. Based on a global compilation of data, we show that functional traits of trees and forest standing biomass explain half of the local variability in forest SOC. The effects of functional traits on SOC depended on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(54 citation statements)
references
References 156 publications
(205 reference statements)
4
49
1
Order By: Relevance
“…Particularly, litter decomposition, nitrogen transformation, and organophosphate mineralization are essential for biogeochemical cycling in forest systems, and functional microbial complexes and microbial community composition play major roles in maintaining soil fertility (Jiao et al, 2021; Wagg et al, 2019). The substrate preferences and survival strategies of bacterial and fungal communities in the forest soil differ (Augusto & Boca, 2022), and their roles and the mechanisms underlying SMC in forest ecosystems, also considering the specific effects on soil vertical spatial scales, are still largely unknown (Jiao et al, 2018; Li, Chen, et al, 2021; Xiong et al, 2021). In the current research, we demonstrate that mixed planting significantly enhances SMC not only in the surface soil but also in the subsurface soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, litter decomposition, nitrogen transformation, and organophosphate mineralization are essential for biogeochemical cycling in forest systems, and functional microbial complexes and microbial community composition play major roles in maintaining soil fertility (Jiao et al, 2021; Wagg et al, 2019). The substrate preferences and survival strategies of bacterial and fungal communities in the forest soil differ (Augusto & Boca, 2022), and their roles and the mechanisms underlying SMC in forest ecosystems, also considering the specific effects on soil vertical spatial scales, are still largely unknown (Jiao et al, 2018; Li, Chen, et al, 2021; Xiong et al, 2021). In the current research, we demonstrate that mixed planting significantly enhances SMC not only in the surface soil but also in the subsurface soil.…”
Section: Discussionmentioning
confidence: 99%
“…The substrate preferences and survival strategies of bacterial and fungal communities in the forest soil differ (Augusto & Boca, 2022) Multi-functionality encompassing multiple interpretable measures in an ecosystem can be used to more accurately describe the status of the ecosystem than any single factor (Hector & Bagchi, 2007;Maestre et al, 2012). To determine multi-functionality, the above-ground vegetation, soil nutrients, physical properties, and functional microbes are considered, to account for major ecological processes in a system (Jiao et al, 2018;Jing et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, late-successional forests such as ours often generally have high soil nutrient concentrations, and nutrient availability is therefore less likely to limit soil respiration [ 35 ]. Instead, the indirect association between total soil elements and soil respiration in our SEMs ( Figure 2 ) suggests that nutrient availability increased soil respiration by promoting plant diversity [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mixing tree species may lead to the expected soil properties based on the proportions of each tree species; however, for several soil properties this is not the case because of antagonistic or synergistic effects instead of pure additive effects (Saetre et al, 1999;Smolander and Kitunen, 2021). Furthermore, biomass over-yielding of mixed forests favours soil C sequestration (Augusto and Boča, 2022). A simulation study showed that in a boreal stand over-yielding was highest in a mixture of the coniferous species Scots pine (Pinus sylvestris L.) and Norway spruce (Picea abies (L.) H.…”
Section: Impact Of Tree Species Selection On Soil C Stockmentioning
confidence: 99%